2018
DOI: 10.3390/sports6040140
|View full text |Cite
|
Sign up to set email alerts
|

The Validity of the Push Band 2.0 during Vertical Jump Performance

Abstract: The Push Band has the potential to provide a cheap and practical method of measuring velocity and power during countermovement vertical jumping (CMJ). However, very little is known about whether it conforms to laboratory-based gold standards. The aim of this study was to assess the agreement between peak and mean velocity and power obtained from the belt-worn Push Band, and derived from three-dimensional motion capture, and vertical force from an in-ground force platform. Twenty-two volunteers performed 3 CMJ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
42
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 27 publications
(46 citation statements)
references
References 18 publications
4
42
0
Order By: Relevance
“…With regards to the reliability of the PUSH Band TM 2.0, the results of this study support previous work that has shown the reliability of the original and PUSH Band TM 2.0 to be acceptable during dumbbell shoulder press and dumbbell curl (Sato et al, 2015), the Smith machine bench press (Perez-Castilla et al, 2019), the back squat (Balsalobre-Fernández et al, 2016;Banyard, Nosaka, Sato, & Haff, 2017), and vertical jumping (Lake et al, 2018;Montalvo et al, 2018;Ripley & McMahon, 2016). However, this counters other work that has considered its reliability during the bench press (Orange et al, 2018).…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…With regards to the reliability of the PUSH Band TM 2.0, the results of this study support previous work that has shown the reliability of the original and PUSH Band TM 2.0 to be acceptable during dumbbell shoulder press and dumbbell curl (Sato et al, 2015), the Smith machine bench press (Perez-Castilla et al, 2019), the back squat (Balsalobre-Fernández et al, 2016;Banyard, Nosaka, Sato, & Haff, 2017), and vertical jumping (Lake et al, 2018;Montalvo et al, 2018;Ripley & McMahon, 2016). However, this counters other work that has considered its reliability during the bench press (Orange et al, 2018).…”
Section: Discussionsupporting
confidence: 88%
“…For each of the two load conditions the trial with the highest mean velocity (from the motion capture data) was selected for further analysis and validity was assessed using data from the different methods from this trial. The trials in which the highest mean velocity (from the motion capture data) occurred were identified on a load-byload and subject-by-subject basis and corresponding peak and mean velocity data from the both methods were taken from these trials (Lake et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A commercially available, inexpensive and user-friendly inertial measurement device is the accelerometer, which has recently gained popularity for measuring a variety of linear and angular spatio-temporal dynamics across weightlifting, kicking, cycling and throwing sports. 8 However, several accelerometers have demonstrated a poor ability to accurately measure linear kinematics during various tasks including powerlifting, 9 resistance exercises (e.g., bench press, squat and deadlift) 10 and athletic movements (e.g., vertical jump) 11 when compared with linear position transducers (LPTs). Therefore, a more plausible means for measuring linear kinematic data might be via LPTs, which use a tethered cord to measure two variables; displacement and time.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies provide support for an enhanced training stimulus with results demonstrating superior improvements in both maximal strength and CMJ performance for individuals following a VBT protocol compared to those following a percentage-based programme [ 12 , 40 ]. However, to perform VBT, a device is required to accurately measure barbell velocity [ 41 ] and the accuracy of some devices have been shown to be limited [ 42 44 ]. In contrast, more accessible methods of autoregulation have been developed that do not require the use of sophisticated measurement devices.…”
Section: The Development Of Autoregulation Of Trainingmentioning
confidence: 99%